Chemical Hydrological Features and Water Quality Evaluation of Phewa Lake of Pokhara Valley Gandaki Province of Nepal - Poudel, Sangita; Mishra, Akkal Dev; Adhikari, Kalpana Gautam (Journal of Nepal Chemical Society, 2023)
This study was conducted to investigate the hydrochemical characteristics and water quality of Phewa lake Pokhara. Water samples were collected and major hydrochemical features were analyzed viz., Transparency, pH, electrical conductivity (EC), total dissolved solids (TDS), total alkalinity (TA), total hardness(TH), dissolved oxygen (DO), microbial analysis (MA), nitrate (NO3¯), phosphate (PO43¯), ammonia(NH3), sulfate (SO42¯), chloride(Cl¯), iron(Fe2+/Fe3+), phosphorus (P) and dissolved solids (DS). The obtained values of the hydrochemical characteristic of lake water have been compared with the world health organization (WHO). The presence of phosphate concentration and the hardness in Phewa lake is higher than the WHO value indicating the problem of rapid eutrophication. This indicates that Phewa lake water has more magnesium and calcium soluble salt. Thus, the rapid eutrophication and higher concentration of organic matter could be a serious problem for lake sustainability. Various types of natural and anthropogenic activities like agricultural runoff, urbanization, discharge of domestic sewage, solid waste dump, and industrial effluent are the major problem for lake sustainability.